2017
DOI: 10.1111/bcp.13360
|View full text |Cite
|
Sign up to set email alerts
|

Unwarranted claims of drug efficacy in pharmaceutical sales visits: are drugs approved on the basis of surrogate outcomes promoted appropriately?

Abstract: Claims of efficacy made in sales visit promotions for drugs approved only on the basis of surrogate outcomes extended beyond the regulator-approved efficacy information for the product in almost half of promotions. Unapproved claims of drug efficacy constitute a form of off-label promotion and merit greater attention from regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In some settings, professionals may lack independent and science‐based continuing education. Promotional information overestimates the benefits of drugs and emphasises positive study results but often omits or minimises the risks . The use of drugs such as mood modifiers, availability of drugs without a medical prescription, and biased media or internet information addressed to patients can also influence expectations about drug benefits.…”
Section: Adrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some settings, professionals may lack independent and science‐based continuing education. Promotional information overestimates the benefits of drugs and emphasises positive study results but often omits or minimises the risks . The use of drugs such as mood modifiers, availability of drugs without a medical prescription, and biased media or internet information addressed to patients can also influence expectations about drug benefits.…”
Section: Adrsmentioning
confidence: 99%
“…Moreover, most of the promotional information is biased. Two studies performed in developed countries found that almost half of the information supplied by pharmaceutical sales representatives made claims beyond the regulator‐approved efficacy information for the product, while mentioning rarely serious adverse events (5–6%), although 45% of promotions had US Food and Drug Administration black box warnings of serious risks . Some information referred to possible ADRs is not easily accessible and can be found only in complex scientific and regulatory information.…”
Section: How To Get Access To Independent and Reliable Information Onmentioning
confidence: 99%